Application development with Qt creator : design and build dazzling cross-platform applications using Qt and Qt Quick - Rischpater, Ray (Community experience distilled., 2014)
This book is great for developers who are new to Qt and Qt Creator and who are interested in harnessing the power of Qt for cross-platform development. If you have basic experience programming in C++, you have what it takes to create engaging cross-platform applications using Qt and Qt Creator!